The influence of endometrial thickness on clinical pregnancy outcomes in early-follicular long-acting and midluteal short-acting GnRH agonist long protocols: a large retrospective study - Wang, Chen; Yang, Congying; Dai, Wei; Han, Liping; Kong, Huijuan; Yao, Guidong; Wang, Xiao; Bu, Zhiqin; Peng, Yuhe; Zhai, Jun (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the impact of endometrial thickness (EMT) variations on clinical outcomes in two distinct ovarian stimulation protocols: the early-follicular long-acting GnRH agonist protocol and the midluteal short-acting GnRH agonist long protocol.MethodsThis retrospective cohort study analyzed 21,290 first-time IVF/ICSI fresh embryo transfer cycles conducted at the Reproductive Center of the First Affiliated Hospital of Zhengzhou University between January 2013 and December 2020. Restricted cubic spline (RCS) analysis was employed to assess the relationship between EMT and clinical pregnancy outcomes.ResultsIn the early-follicular long-acting GnRH agonist protocol group, both clinical pregnancy and live birth rates increased with EMT up to 10.6 mm, beyond which the rates plateaued. Conversely, in the midluteal short-acting GnRH agonist long protocol group, a continuous positive correlation was observed between EMT and both clinical pregnancy and live birth rates. Overall, the early-follicular long-acting protocol demonstrated superior pregnancy outcomes compared to the midluteal short-acting protocol when EMT was less than 15 mm. However, when EMT was ≥15 mm, both protocols yielded comparable clinical pregnancy and live birth rates.ConclusionThe study indicates that in the early-follicular long-acting GnRH agonist protocol, increasing EMT up to 10.6 mm is associated with improved clinical pregnancy and live birth rates, with no further benefits observed beyond this threshold. In contrast, the midluteal short-acting GnRH agonist long protocol exhibits a continuous positive relationship between EMT and pregnancy outcomes. Overall, the early-follicular long-acting protocol offers better clinical outcomes for patients with EMT less than 15 mm, while both protocols perform similarly when EMT is ≥15 mm.